HTA as a framework for task analysis. - Shepherd A (Ergonomics)
The motivation for this paper is to review the status of Hierarchical Task Analysis (HTA) as a general framework for examining tasks, including those for which cognitive task analysis methods might be assumed to be necessary. HTA is treated as a strategy for examining tasks, aimed at refining performance criteria, focusing on constituent skills, understanding task contexts and generating useful hypotheses for overcoming performance problems. A neutral and principled perspective avoids bias and enables the analyst to justify using different analytical methods and develop hypotheses as information is gained about the task. It is argued that these considerations are equally valid when examining tasks that are assumed to contain substantial cognitive elements. Moreover, examining cognition within the context of a broader task helps to situate cognition within the network of actions and decisions that it must support, as well as helping to establish where effort in cognitive task analysis is really justified.